1989
DOI: 10.1172/jci114058
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and nucleotide sequence of complementary DNAs encoding human short chain acyl-coenzyme A dehydrogenase and the study of the molecular basis of human short chain acyl-coenzyme A dehydrogenase deficiency.

Abstract: Complementary DNAs encoding the precursor of human placental short chain acyl-coenzyme A (CoA) dehydrogenase (SCAD) (EC 1.3.99.2) were cloned and sequenced. The cDNA inserts in these clones were 1,852 bases in length combined, and encoded the entire 412-amino acid precursor SCAD (mol wt 44,303). This sequence included the 24-amino acid leader peptide moiety (mol wt 2,576) and 388 amino acids corresponding to the mature protein (mol wt 41,727). The comparison of SCAD and medium chain acyl-CoA dehydrogenase sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…This suggested that the defect of SCAD in these patients is caused by a point mutation in the SCAD gene (3). Furthermore, using immunoblot analysis and pulse-chase experiment, we showed that variant SCAD synthesized by the cells from one of the patients, reported by Amendt et al as L.N.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…This suggested that the defect of SCAD in these patients is caused by a point mutation in the SCAD gene (3). Furthermore, using immunoblot analysis and pulse-chase experiment, we showed that variant SCAD synthesized by the cells from one of the patients, reported by Amendt et al as L.N.…”
Section: Introductionsupporting
confidence: 62%
“…our previous studies (3,4), we have shown that the cells from all three patients synthesized a variant SCAD protein of normal size. This suggested that the defect of SCAD in these patients is caused by a point mutation in the SCAD gene (3).…”
Section: Introductionmentioning
confidence: 54%
“…In humans, loss of function mutations have been identified in genes encoding SCAD (ACADS [37]), MCAD (ACADM [38]. ), VLCAD (ACADVL [39]), and CPT-1A [40], but not CPT-1B or LCAD [41].…”
Section: Discussionmentioning
confidence: 99%
“…Subunits of the SCAD enzyme are nuclear encoded and synthesized in the cytosol as precursor proteins that are imported into the mitochondrial matrix. Newly imported SCAD proteins are proteolytically processed, folded, and assembled into the biologically active homotetrameric form (168 kDa) containing one molecule of FAD per subunit (2). Hereditary deficiency of SCAD has been reported in 20 patients world-wide with a variety of clinical symptoms (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…This agrees with the mutation spectrum observed in a larger group of SCAD patients. 2 Because the common SCAD variants are detected in 14% of the general population, they cannot be sufficient to cause SCAD deficiency. The role of 625GϾA and 511CϾT in the pathogenesis of SCAD deficiency, therefore, is not clear.…”
mentioning
confidence: 99%